On determining grammatical relations in Slave* ... - Hildebrand, Joyce L (University of Calgary, 1985)
Although there is an extensive literature on the analysis of Athapaskan languages, the emphasis has been on the verbal morphology and the phonological systems of these languages. This focus is understandable, given the complexity of the verbal morphology of Athapaskan languages and the difficulty encountered in attempts to describe their syntax within any current theoretical framework. In this paper, however, I will concentrate on a syntactic phenomenon in Slave, a northern Athapaskan language, referring to the verbal morphology only as it relates to the phenomenon under discussion. ...